Prevention of secretory diarrhea by ethanol extract of Bistortae rhizoma through inhibition of chloride channel (Bangladesh Journal of Pharmacology, 2015)
Inhibition of cystic fibrosis transmembrane conductance regulator (CFTR) and Ca2+-activated Cl- channel (CaCC) represents an attractive approach for the treatment of secretory diarrhea. The aim of the study is to investigate the molecular basis of the anti-diarrheal effect of traditional Chinese herbal anti-diarrheal medicine Bistortae rhizoma. Fluorescence quenching assay indicated that the 40% methanol /water fraction (D5) dose-dependently inhibited both CFTR and CaCC function in transfected Fischer rat thyroid (FRT) cells. Ex vivo studies indicated that D5 inhibited both forskolin (FSK)-activated CFTR current and CCh-induced CaCC current in rat colonic mucosa. In the mouse closed-loop model, intraluminal application of D5 (200 µg/mL) significantly reduced cholera toxin-stimulated fluid secretion. In the intestinal motility model, D5 significantly delayed intestinal peristalsis in mice. Our research suggests that CFTR and CaCC-mediated intestinal epithelial Cl- secretion inhibiting and gastrointestinal motility delaying may account for the anti-diarrheal activity of B. rhizoma.